Elaboración de una guía didáctica de juegos empleando ejes trasversales, para la protección del medio ambiente, en la ludoteca de la Universidad Técnica de Cotopaxi del cantón Latacunga de la provincia de Cotopaxi en el periodo 2011 – 2012 - Proaño Defaz, María Isabel (2014)
The present investigation deals about environment protection in order to encourage children love and nature preservation, being the cornerstone teachers to encourage them to create the integral of each managing to create a methodology own education in helping to motivate and care for nature is paramount in the children development because it helps them become adults, healthy, creative, conscious with values and welfare of our planet and motivating them to the mission of caring for the environment by developing their intellectual and human capacities so they can reach their full learning potential. Children help to protect the environment should be necessary tools that help in the practice of many activities, which is based on what they like most children, play, is important to emphasize that it is necessary to have instruments that needed this game library as an educational guide developed based on the game, putting emphasis on transverse axes, especially the care and environment preservation, which is very prominent problem because children who at tend establishments educational as well as teachers have failed to build a true culture respect and love the nature. The game is a natural and innate activity for allowing the child to have an interest in nature being a recreational activity that provides entertainment and fun, little by little, the inner structure of the child grows along with their values developed from their early years his personality.